South Africa : 2007 Article IV Consultation -Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for South Africa. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that real GDP in South Africa grew by 5 percent in 2006 and continued to grow vigorously in early 2007. Growth was driven by strong domestic demand, with private consumption and investment spending supported by continuing robust consumer and business sentiment and low interest rates until late 2006. Asset prices continued to rise rapidly in 2006 and early 2007. Executive Directors have considered that the economic outlook for South Africa remains broadly positive.